Columnar optical properties of locally emitted light-absorbing carbonaceous aerosols - Kang Hu; Hong Liao; Dantong Liu; Jianbing Jin; Siyuan Li; Yangzhou Wu; Yuxing Gao; Xiaotong Jiang; Shitong Zhao; Ping Tian; Fei Wang; Na Kang; et al. (Journal of Environmental Sciences, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

Solvation engineering of dual-polymer gel electrolyte via competitive coordination effect for durable lithium metal batteries - Xiaoya Qu; Na Li; Hao Zhai; Zhengyuan Bai; Yong Liu; Hao Wang; Shu Hong; Zhenyue Xing; Xiaodong Shi; Peng Wang (Chemical Engineering Journal, 2026)

Amino-engineered interfacial photocatalytic membrane with enhanced antifouling and self-cleaning performance for sustainable water purification - Qiaozhi Wang; Qi Zhang; Na Qi; Yehao Yan; Yan Zhang; Ensheng Xu; Hong Chen; Ziyi Wu; Zehui Zhao; Dan Huang; Qingwang Xue; Ying Li; et al. (Chemical Engineering Journal, 2026)

Enhancing bread storage stability with chitosan oligosaccharides of different molecular weights: inhibiting spoilage microorganisms and retarding starch retrogradation - Li-Hong Du; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Carbohydrate Polymers, 2026)

Green synchronous fluorescence spectroscopy using non-carcinogenic standard: Rapid determination of carcinogenic polycyclic aromatic hydrocarbons in dairy products - Yi-Han Guo; Jia-Rong He; Jia-Wen Wei; Hong-Jun Liu; Jia-Lin Li; Ping-Ping Wu; Gaofeng Zheng; He-Dong Luo; Na Li; Yao-Qun Li (Food Control, 2026)

Short-term silica inhalation triggers sustaining pulmonary fibrosis in a rat recovery model - Xinyue Yang; Yinong Hai; Yuqi Chen; Dingjie Xu; Yaqian Li; Fuyu Jin; Zhongqiu Wei; Ying Zhu; Xuemin Gao; Wenchen Cai; Tian Li; Na Mao; et al. (Food and Chemical Toxicology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

High-fidelity phase-change transfer platform for laser-induced graphene toward multifunctional flexible electronics - Zhao Li; Yanping Song; Wenjie Shao; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Zhuang Miao; Shudong Zhang; Cui Liu; Min Xi; et al. (Chemical Engineering Journal, 2026)

Molecular understanding of plant pollination, fertilization, seed development and protoplast regeneration - Jiang-Guo Meng; Pu Liu; Hanxian Xiong; Wei Wang; Gang Xu; Xu Xin; Zijun Lan; Changkai Ma; Na Wang; Xuecheng Zhang; Ce Shi; Shu Chang; et al. (Science China Life Sciences, 2026)
Sexual reproduction in plants is a tightly coordinated process that underpins biodiversity, drives speciation, and serves as a foundation for modern crop improvement. Here, we synthesize recent advances in elucidating the molecular mechanisms governing major reproductive events in flowering plants, including male and female gametogenesis, pollen-pistil communication, double fertilization, embryogenesis, and endosperm-mediated seed development. We also discuss the integration of asexual propagation through protoplast regeneration, highlighting its emerging importance in plant biotechnology. Together, these insights deepen our understanding of fundamental reproductive biology and open new opportunities for the rational design of hybrid breeding systems and stress-resilient crops, with broad implications for global food security under changing climatic conditions.

Effects of GIAHS conservation on agricultural landscape and ecological sustainability in heritage sites: evidence from the Yuanyang Hani Rice Terraces - Jin-Rong Zhang; Hong-Bo Li; He-Ping Yang; Meng-Na Qi (Environment, Development and Sustainability, 2026)

Physicochemical characteristics changes in post-ripening of wheat flour mill streams: Effects on dough properties and steamed bread quality - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Protective effects of melatonin on mouse ovarian tissue against oxidative stress and ferroptosis may involve the MT1 receptor - Sheng Nan Jiang; Xin Zhang; Li Na Si; Meng Wei; Xin Hui Wei; Yong Wei Wang; Tie Cheng Sun; Song He Yang; Zhi Hong Chen; Lu Yang Cheng (Cryobiology, 2026)

How does residential and daily green space exposure promote individual mental health in the suburbs? A study via multiple pathways - Hong Li; Jiayu Wu; Na Ta (Applied Geography, 2026)

Post-earthquake road accessibility assessment in mountainous counties incorporating geological hazard density correction: A case study of Pingshan County, Hebei Province - Qiu-na Guo; He Zhang; Hong-yu Wang; Fan Yang; Jiang Li; Si-yu Liu (Applied Geophysics, 2026)

Retraction notice to “Characterization, quantification and application of energy flexibility in office building: A comprehensive review” [Energy Build. 347 (2025) 116306] - Bilal Ahmed; Ateeque Ahmed; Hong-Na Zhang; Xiao-Bin Li; Kai-Yang Qu; Feng-Chen Li (Energy and Buildings, 2026)

Rational structuring engineering of a hydrogenation-dominated air electrode with Ag exsolution for reversible protonic ceramic cells - Dong Zhang; Ruinan Wang; Xi Chen; Na Yu; Mengxuan Zeng; Guanzhen Li; Yanya Liu; Meijing Hong; Shuo Zhai; Meng Ni (Chemical Engineering Journal, 2026)

Schisandrin B targets CD44 to inhibit glioblastoma multiforme - Na Wang; Yuxin Xie; Jialin Chen; Wenpei Chen; Donghao Zhang; Hong Li (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

A state-of-the-art review of accurate and rapid prediction methods for thermal striping phenomenon in nuclear reactors - Mohsin Raza; Ikram UI Haq; Waqar ul Hassan; Jun-Liang Guo; Hong-Na Zhang; Xiao-Bin Li; Yue Wang; Wei-Hua Cai; Shu-Qi Meng; Fang Chen; Yu-Long Mao; Feng-Chen Li (Annals of Nuclear Energy, 2026)

Exploring the impact of dietary extracellular vesicles on gut health: homeostasis, barrier defense, immunity, and signaling pathways - Haiyan Zhang; Jianing Tu; Yue Pang; Jiahui Ma; Lin Zhang; Chenyu Xue; Yuhao Liu; Weichen Hong; Mizhou Hui; Bailiang Li; Na Dong; Chenzhe Gao (Food Research International, 2026)

Improvement of the quality of whole grain highland barley slurry through thermal pre-treatment under turbulent conditions: Lubrication, microstructure, and rheological - Bo-Hui Li; Yi-Peng Bai; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Chemistry, 2026)

Erzhi pills: a potential aging-modulating agent targeting immunosenescence in mice - Zhirui Fang; Wei Sun; Na Li; Tingting Shi; Xiuyun Ren; Rui Zhang; Yujing Zhang; Jing Chen; Qi Liu; Meng Wang; Lu Chen; Hong Wang (Biogerontology, 2026)

Impacts of gluten aggregation behavior on the gassing properties of steamed bread during the wheat flour post-ripening - Meng-Li Zhang; Xiao-Na Guo; Xiao-Hong Sun; Ke-Xue Zhu (Food Hydrocolloids, 2026)

Multifunctional pomelo peel cellulose/lysine/ZIF-8 porous foam with honeycomb structure: Adsorption performance and mechanism - Haize Su; Weipeng Qiu; Tenggen Hu; Shaohua Luo; Jinling Wu; Xiaowen Zhong; Na Li; Hao Su; Zhizhou Ling; Zhenlin Xu; Hong Wang; Peng Wen (Carbohydrate Polymers, 2026)

Two new abietane diterpenoids from Salvia cavaleriei var. simplicifolia - Qian Wu; Jie Yang; Mi-Na Yang; Li-Jia Ye; Hong-Fen Jiang; Miao Zhang; Xin Wang; Yi-Nan Yang; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2026)

Long-term waterproof performance of EPDM sealing gaskets considering aging-induced stress relaxation - Hua-Yong Li; Huai-Na Wu; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Impacts of iron additives on enzymatic activities and nitrogen cycling during composting: Microbial and biochemical insights - Yang Wang; Hong-Yi Wu; Shuang-Yan Jia; Hao-Duo Bai; Kuok Ho Daniel Tang; Xiu-Na Ren; Zhixin Zhang; Yao Yiqing; Guo Xiaohui; Chugang Mei; Rong-Hua Li (Journal of Cleaner Production, 2026)

The Lithosphere-Atmosphere-Ionosphere coupling (LAIC) processes around the 2024 Wushi (China) Mw7.1 earthquake - Xuemin Zhang; Angelo De Santis; Pan Xiong; Gianfranco Cianchini; Aisa Yisimayili; Saioa A. Campuzano; Na Yang; Serena D’Arcangelo; Jing Liu; Mariagrazia De Caro; Xinyan Li; Cristiano Fidani; et al. (Journal of Asian Earth Sciences, 2026)

Synergistic engineering of a whole-cell catalyst immobilized on bimetallic CaZn-MOF for efficient PET Depolymerization - Yun-kang Chang; Xiao-huan Liu; Nan-Li; Jun-li Jin; Hai-tong Sun; Shuo Li; Fei-fei Zhang; Yu-xuan Song; Xin-hong Yu; Qi-zhi Cao; Fei Liu; Na Xu; et al. (Chemical Engineering Journal, 2026)

Prediction on the waterproof performance of EPDM gaskets in shield tunnels considering the stress state of compression and tension - Ren Wu; Huai-Na Wu; Hua-Yong Li; Xin-Xin Yang; Dong-Lin Feng; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Application of an innovative BMask R-CNN-DAT enhanced with feature extraction and boundary awareness in tunnel leakage detection - Yu Li; Huai-Na Wu; Hong-Zhan Cheng; De-Sai Guo; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Comprehensive analysis of metabolic response in Arabidopsis thaliana under heavy metal stress by mass spectrometry - Zhongyan Zhou; Donghao Li; Na Wang; Xiujuan Hong; Wen Su; Cheng Guo; Chongsheng He; Lei Yue (Journal of Hazardous Materials, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

GAS1 affects proliferation, apoptosis, and steroid hormone levels by regulating mitochondrial functions and the PI3K/AKT pathway in bovine granulosa cells - Wenjie Yu; Na Pei; Haitao Jia; Yijing Yin; Hong Xu; Tian Tian; Chang Liu; Lingxia Xu; Ze Li; Zibin Liu; Xiaoshi Cai; Mingkai Yu; et al. (Theriogenology, 2025)

Synoptic-scale precipitation events recorded by high-resolution intra-shell δ18O of land snail in the Asian monsoon marginal zone - Qian Zhang; Jibao Dong; Guozhen Wang; Fan Luo; Ya-na Jia; Chengcheng Liu; Xiulan Zong; Xiangzhong Li; John Dodson; Hong Yan (Quaternary Science Reviews, 2025)

Corrigendum to “Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar” [Food Res. Int. 175 (2024) 113742] - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Unveiling regulatory network of porcine oocyte IVM using integrated multi-omics - Yufen Jiang; Helin Li; Na Cheng; Yuchen Han; Qiue Xu; Mingjin Li; Muhammad Ameen Jamal; Jianxiong Guo; Honghui Li; Hong-Jiang Wei; Wenmin Cheng (Livestock Science, 2025)

Smoldering heterogeneous oily sludge: Key influencing factors - Yi Lin; Zehua Luo; Fuli Li; Chih-Huang Weng; Yanru Hao; Na Liu; Mei Hong (Journal of Cleaner Production, 2025)

Sensitive detection of diazinon and bioaccumulation monitoring in crops enabled by cu-sealed metal-organic framework nanosystem with target-responsive aggregation-induced emission - Jie Tang; Tingting Cai; Zexi Chen; Na Li; Jintong Liu; Hong Yang (Food Chemistry, 2025)

RETRACTED: Characterization, quantification and application of energy flexibility in office building: A comprehensive review - Bilal Ahmed; Ateeque Ahmed; Hong-Na Zhang; Xiao-Bin Li; Kai-Yang Qu; Feng-Chen Li (Energy and Buildings, 2025)

Cyano cyclization-anchoring strategy breaks the activity-stability trade-off in COF photocatalysts - Xia-Jun Jin; Jing-Qi Liu; Hong-Xia Zhang; Qiang-Qiang Yu; Hong-Zhi Zhou; De-Ming Kong; Li-Na Zhu (Chemical Engineering Journal, 2025)

Investigation of the South Atlantic Anomaly (SAA) by proton flux variabilities based on 6 years’ CSES data - Lu Wang; Zhenxia Zhang; Xinqiao Li; Zhenghua An; Yanbing Xu; Ping Wang; Hong Lu; Xiaoyun Zhao; Dali Zhang; Xiaohua Liang; Zhiqiang Ding; Shujie Li; et al. (Science China Earth Sciences, 2025)

PEDUNCLE LENGTH 1 regulates wheat peduncle elongation through brassinosteroid signaling pathway - Hong Liu; Liya Zhi; Hualiang Qiao; Yanxiao Niu; Jianxiu Shang; Hao Zhang; Wenzhao Xie; Yazhou Xuan; Wenqing Li; Jijie Li; Xinyu Zhang; Liuge Xue; et al. (Molecular Plant, 2025)

Erratum to ‘mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source’[Food Chemistry 481 (2025) 144069] - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

Laser-engineered carbon hierarchies with multiscale attenuation mechanisms for ultrabroadband microwave absorption - Zhao Li; Nian Li; Yanping Song; Jun Kang; Na Hong; Shuai Han; Shihao Wang; Zhiyuan Yang; Shudong Zhang; Cui Liu; Min Xi; Congfa Song; et al. (Chemical Engineering Journal, 2025)

Establishment of an ELISA for the detection of antibodies against Stenotrophomonas maltophilia - Qian Zhang; Lu Dai; Fuxian Zhang; Zijie Xu; Xiangrui Yang; Hong Chu; Guangmou Yan; Na Li; Fengyang Li; Liancheng Lei (Veterinary Research Communications, 2025)

CD39 activities in the treated acupoints contributed to the analgesic mechanism of acupuncture on arthritis rats - Yu-Jia Li; Jie Lin; Si-Qi Tang; Wei-Min Zuo; Guang-Hong Ding; Xue-Yong Shen; Li-Na Wang (Purinergic Signalling, 2025)

Metabolome and Genome Analysis of a Novel Endophytic Fungus Aureobasidium pullulans KB3: Discovery of Polyketones and Polyketone Biosynthesis Pathway - Shuai Wang; Jia-Nuo He; Ying-Jie Wang; Wen-Ya Zhao; Qing-Xia Yang; Ya-Na Wang; Yang Zhang; Li-Ping Zhang; Hong-Wei Liu (Biochemical Genetics, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Target-induced dissociation of AIE metal-organic framework for ﬂuorescence-enhanced determination of the chlorpyrifos bioaccumulation in wheat by employing Mn (III) as the active center - Jie Tang; Tingting Cai; Na Li; Zexi Chen; Jintong Liu; Hong Yang (Journal of Hazardous Materials, 2025)

Mechanisms of exopolysaccharide synthesis by Streptococcus thermophilus IMAU20246 determined by the carbon source - Qingting Peng; Haimin Hu; Annaer Dai; Na Wu; Hong Li; Tong Dan (Food Chemistry, 2025)

Exploring food-derived bioactive peptides: Efficacy, mechanisms, and clinical implications in ferroptosis regulation - Chenzhe Gao; Lin Zhang; Jiahui Ma; Haiyan Zhang; Yue Pang; Chenyu Xue; Dehai Li; Xiaoyu Zhao; Munkh-Amgalan Gantumur; Mizhou Hui; Weichen Hong; Yihong Bao; et al. (Trends in Food Science & Technology, 2025)

The effect of 254 nm ultraviolet C promoting ethanol-induced gastric injury healing - A potential physical factor therapy - Xiao Zhang; Dong-mei Li; Hong-long Chen; Xi-sheng Lin; Su-su Li; Le Yu; Nan Peng; Li-kang Wang; Na Wang; Yue-ming Gao (Journal of Photochemistry and Photobiology B: Biology, 2025)

Maintaining the sustainability of energy-saving behavior: A comprehensive analytical framework based on empirical evidence and game theory - Shuhan Yang; Ruyin Long; Hong Chen; Shiyan Jiang; Jiawei Chen; Jingwen Na; Qian Li (Journal of Environmental Management, 2025)

Self-assembled TMB-CuO2 nanosheets for dual-mode colorimetric and NIR-II photothermal detection of uranyl ion - Yingying Wu; Xiaofeng Tan; Hongyu Gong; Minghui Wang; Gui-long Wu; Na Li; Fen Liu; Hong Xia; Li Tang; Qinglai Yang (Analytica Chimica Acta, 2025)

Corrigendum to ‘What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population?’ [Environ. Pollut. 345 (2024) 123499] - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2025)

Widely targeted metabolomics analysis reveals dynamic changes in metabolites of 'Hass' avocado during postharvest ripening period - Ying Xin; Na Li; Hong-Tao Zhu; Ya-Zhi Li; Han-Zhang Xiang; Jia-Huan Shang; Man Zhang; Ying-Jun Zhang (Food Chemistry, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

How to promote sustainable recycling of plastic packaging waste? A study combining machine learning with gaming theory - Shuhan Yang; Ruyin Long; Hong Chen; Jingwen Na; Qingqing Sun; Ting Yue; Qianwen Li; Xinru Wang; Wanqi Ma; Mark Goh (Environmental Impact Assessment Review, 2025)

Semi-sacrificial fabrication of binder-free lithium-aluminum layered double hydroxides adsorbents for lithium extraction - Jinqiang Gao; Mei Hong; Jiatao Zhong; Shengnan Na; Yuqing Su; Han Li; Mingyu Hu; Shihe Yang (Desalination, 2025)

Microwave-responsive nanoencapsulated fluorescence thermometers for quantitative assessment of microscale localized heat regulation in chemical production - Kai Liu; Na Wang; Zongliang Kou; Xiaxin Jiao; Suguang Yang; Minghui Lyu; Hong Li; Zhenyu Zhao; Xin Gao (Chemical Engineering Journal, 2025)

Structure characteristics of a novel pectic polysaccharide from Fructus Corni and its protective effect on alcoholic fatty liver - Hong-Xin Bai; Yu-Xuan Gao; Shuyao Wang; Guang-Yuan Ma; Wenjing Zhao; Xiao-Qiang Li; Yu-Fan Wang; Qiu-Na Nong; Yu-Bo Wang; Jin Tan; Qimei Duan; Wei Cao (Carbohydrate Polymers, 2025)

KCNJ15 inhibits chemical-induced lung carcinogenesis and progression through GNB1 mediated Hippo pathway - Hong-qiang Chen; Na Wang; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Ya-wen Li; Shuang-wu Deng; Zi-yuan Zhou; Wen-bin Liu (Toxicology, 2025)

Engineering a circular DNA agonist to activate MET signaling for promoting angiogenesis and regeneration of diabetic ulcer - Jun Zhu; Meixia Wang; Zhu Li; Ceheng Liao; Yangbing Li; Zhixi Duan; Xinxin Zhang; Yizhi Zhang; Fang He; Zhou Nie; Hong-Hui Wang; Na Cai; et al. (Chemical Engineering Journal, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Foxa1 disruption enhances human cell integration in human-mouse interspecies chimeras - Li-na Wang; Jun-shuang Jia; Xing-long Yang; Yue-ting Wen; Jing-xian Liu; Deng-ke Li; Xing-rui Chen; Jia-hong Wang; Ji-ke Li; Zhong-xi Huang; Kai-tai Yao (Cell and Tissue Research, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

Season-dependent climate sensitivity of the surface runoff of major rivers in Changbai Mountain - Xinran Li; Hong S. He; Na Li; Heyuan Yu; Shengwei Zong; Zhengfang Wu; Haibo Du (Journal of Hydrology, 2024)

RNA reading protein YTHDF2 mediates Benzo(k)fluoranthene induced male reproductive injury by regulating the stability of BCL2 - Ya-wen Li; Dan-dan Wang; Hong-qiang Chen; Yong Zeng; Na Wang; Yu Shi; Jiang-ying Li; Ni-ya Zhou; Da-peng Wang; Qing Chen; Xue Han; Jia Cao; et al. (Environmental Pollution, 2024)

Seismic behavior and resilience assessment of prefabricated beam–column joint with replaceable graded-yielding energy-dissipating connectors - Yongfeng Du; Fangyu Li; Hu Li; Na Hong; Peihong Chi (Engineering Structures, 2024)

Phase change thermal interface film with bicontinuous and textured filler network for efficient wearable heat dissipation - Jia-Qing Zhao; Xiang Wang; Xun-Rui Wang; Hong-Wei Zhao; Mei-Na Lu; Wayne-Qiang Xu; Hong-En Nian; Jin-Hong Li (Chemical Engineering Journal, 2024)

Development and application of turbulent heat flux model for lead-bismuth eutectic based on deep learning - Li-Xia Chen; Chao Yuan; Jun-Long Zhao; Hong-Na Zhang; Xiao-Bin Li; Feng-Chen Li (Annals of Nuclear Energy, 2024)

The comparative techno-economic and life cycle assessment for multi-product biorefinery based on microwave and conventional hydrothermal biomass pretreatment - Na Wang; Kai Liu; Zhengkun Hou; Zhenyu Zhao; Hong Li; Xin Gao (Journal of Cleaner Production, 2024)

Multiple strategy for antibacterial effect via copper porphyrin doping polyphenolic aldehydes based covalent organic framework - Zi-Wen Zhou; Chun-Xiu Liu; Chun-Xian Cai; Yun-Jie Wei; Kun Li; Xiao-Qi Yu; Yan-Hong Liu; Na Wang (Journal of Environmental Chemical Engineering, 2024)

FTO mediates bisphenol F-induced blood-testis barrier impairment through regulating ferroptosis via YTHDF1/TfRc and YTHDF2/SLC7A11 signal axis - Yu Shi; Li Yin; Jiang-ying Li; Shi-meng Zhou; Na Wang; Hong-qiang Chen; Yong Zeng; Ya-wen Li; Wen-bin Liu (Environmental Pollution, 2024)

Heterostructure-anchored 3D CNT-bridged graphene architecture via layer-by-layer structural engineering for thick electrodes of supercapacitors - Yanping Song; Nian Li; Jun Kang; Zhao Li; Na Hong; Shuai Han; Liqing Chen; Shudong Zhang; Cui Liu; Congfa Song; Jiakuan Zhang; Zhenyang Wang (Chemical Engineering Journal, 2024)

Benzo(a)pyrene promotes the malignant progression of malignant-transformed BEAS-2B cells by regulating YTH N6-methyladenosine RNA binding protein 1 to inhibit ferroptosis - Na Wang; Hong-qiang Chen; Yong Zeng; Yu Shi; Zhe Zhang; Jiang-ying Li; Shi-meng Zhou; Ya-wen Li; Shuang-wu Deng; Xue Han; Zi-yuan Zhou; Mao-lin Yao; et al. (Toxicology, 2024)

Paospora carinifang n. gen., n. sp. (Microsporidia: Spragueidae), a parasite of the ridgetail white prawn, Palaemon carinicauda - Yuan Wang; Ying Na; Yan-qing Huang; Jun-fang Zhou; Shou-hu Li; Quan-lin Liu; Le-tian Li; Yuan-ge Chen; Wei Tian; Hai Chi; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2024)

Biochar with KMnO4-hematite modification promoted foxtail millet growth by alleviating soil Cd and Zn biotoxicity - Xirui Kang; Na Geng; Yaping Li; Wei He; Hui Wang; Hong Pan; Quangang Yang; Zhongchen Yang; Yajie Sun; Yanhong Lou; Yuping Zhuge (Journal of Hazardous Materials, 2024)

Triple modal aptasensor arrays driven by CHA-mediated DNAzyme for signal-amplified atrazine pesticide accumulation monitoring in agricultural crops - Jintong Liu; Na Li; Linyao Ye; Lin Zhou; Guanghao Chen; Jie Tang; Heng Zhang; Hong Yang (Journal of Hazardous Materials, 2024)

Safety and environmental protection application of high performance solid waste unburned ceramsite and its lightweight high strength concrete - Kai-jing Tang; Hong-na An; Chuan-bei Liu; Ying-ding Li; Lu-jun Jia; Yun Tang; Qi-qiang Wang; Yong Jiang; Zi-jian Song (Sustainable Chemistry and Pharmacy, 2024)

Conformational transformation of activator strand directly regulates CRISPR/Cas12a system activity for live cell sensing of multiple biomolecules - Qing-Nan Li; Dong-Xia Wang; Zhi-Qi Dai; Shun-Li Wu; Gui-Mei Han; Sha Lu; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Chemical Engineering Journal, 2024)

An efficient microwave-assisted method using ethyl lactate/water cosolvent for lignocellulosic biomass fractionation - Na Wang; Kai Liu; Anran Xu; Hong Li; Zhenyu Zhao; Xiaolei Fan; Xin Gao (Chemical Engineering Journal, 2024)

Phenolic constituents with potent α-glucosidase inhibitory and cytotoxic activities from Rumex nepalensis var. remotiflorus - Jing-Juan Li; Xin-Xin Wang; Yuan-Meng Li; Na Li; Hong-Tao Zhu; Komila Alibekovna Eshbakova; Ying-Jun Zhang (Phytochemistry, 2024)

An alkali-extracted neutral heteropolysaccharide from Phellinus nigricans used as an immunopotentiator in immunosuppressed mice by activating macrophages - Feihe Wang; Na Li; Hong Li; Yao Di; Fan Li; Peng Jiang; Guiyun Wang (Carbohydrate Polymers, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Enhancing proton transport in polyvinylidenedifluoride membranes and reducing biofouling for improved hydrogen production in microbial electrolysis cells - Na Zhao; Shujuan Meng; Xiaohu Li; Hong Liu; Dawei Liang (Bioresource Technology, 2024)

Genome-wide analysis of in vivo-evolved Candida auris reveals multidrug-resistance mechanisms - Xin-Fei Chen; Han Zhang; Ling-Li Liu; Li-Na Guo; Wen-Jing Liu; Ya-Li Liu; Ding-Ding Li; Ying Zhao; Ren-Yuan Zhu; Yi Li; Rong-Chen Dai; Shu-Ying Yu; et al. (Mycopathologia, 2024)

Assessment of the comprehensive carrying capacity of the central plains urban agglomeration in the Yellow River Basin, China - Shuhan Yang; Ruyin Long; Hong Chen; Meifen Wu; Qianwen Li; Yujie Wang; Xinru Wang; Jingwen Na (Environment, Development and Sustainability, 2024)

Two new degrade triterpenoids from Buxus bodinieri Levl. - Yu-Xin Yan; Na-Li Song; Ji-Hong Zhang; Ming-Hua Qiu (Natural Product Research, 2024)

Regional variations in management and outcomes of patients with acute coronary syndrome in China: Evidence from the National Chest Pain Center Program - Shuduo Zhou; Yan Zhang; Xuejie Dong; Junxiong Ma; Na Li; Hong Shi; Sidney C. Smith; Yinzi Jin; Ming Xu; Dingcheng Xiang; Zhi-Jie Zheng; Yong Huo (Science Bulletin, 2024)

An electro-ferroptotic nanoammunition enables image-guided, spatiotemporally controlled cancer ferroptosis induction via irreversible electroporation - Jun-Hyeok Han; Hee Seung Seo; Jiyoung Lee; Zheng Chen; Qiyue Wang; Yun Young Lee; Na Kyeong Lee; Jeon Min Kang; Song Hee Kim; Hwichan Hong; Jung-Hoon Park; Yuanzhe Piao; et al. (Chemical Engineering Journal, 2024)

Genome constitution and evolution of Elymus atratus (Poaceae: Triticeae) inferred from cytogenetic and phylogenetic analysis - Lu Tan; Dan-Dan Wu; Chang-Bing Zhang; Yi-Ran Cheng; Li-Na Sha; Xing Fan; Hou-Yang Kang; Yi Wang; Hai-Qin Zhang; Marcial Escudero; Yong-Hong Zhou (Genes & Genomics, 2024)

Polar peripheral substituent-regulated organic/inorganic hybrid photocatalysts promoting the degradation of phenolic pollutants - Sheng-Hua Ma; Wei-Liang Jin; Hong-Xia Zhang; Shao-Cong Li; De-Ming Kong; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Molecular mechanism of efficient degradation of TPM dyes by Serratia species WKD at high temperature - Yi Wei; Xin-Jiao Dong; Gang Li; Huan Wu; Lin-Na Du; Jia-Cheng Zhou; Jun Zhang; Yan-Ping Xiao; Yue-Mei Shang; Hong-Xia Liu (International Biodeterioration & Biodegradation, 2024)

Melting-salt crystallization assisted controllable synthesis of core-shell zeolite catalyst for effective coupling of microwave hotspot and catalytic active site - Kai Liu; Qiuyan Ding; Na Wang; Zongliang Kou; Anran Xu; Hong Li; Zhenyu Zhao; Yilai Jiao; Xin Gao (Chemical Engineering Journal, 2024)

Understanding the causes of rapidly declining prediction skill of the East Asian summer monsoon rainfall with lead time in BCC_CSM1.1m - Na Wang; Hong-Li Ren; Yi Deng; Siyu Zhao (Climate Dynamics, 2024)

Pigmentiphaga kullae CHJ604 improved the growth of tobacco by degrading allelochemicals and xenobiotics in continuous cropping obstacles - Jia-Xi Xiong; Ling-Shan Du; Na-Na Li; Xiu-Ting Wu; Yang Xiang; Sha Li; Lei Zou; Dongqi Liu; Duo Huang; Ze Feng Xie; Ying Wang; Jinhua Li; et al. (Journal of Hazardous Materials, 2024)

Always positive covalent organic nanosheet enabling pH-independent adsorption and removal of Cr(Ⅵ) - Dong-Xiao Cao; Yun-Jie Zhou; Hong-Xin Jiang; Xue-Nan Feng; Xiao-Yang Liu; Wei Li; Jing-Qi Liu; An-Na Tang; De-Ming Kong (Journal of Hazardous Materials, 2024)

AOB Nitrosospira cluster 3a.2 (D11) dominates N2O emissions in fertilised agricultural soils - Na Deng; Cecile Gubry-Rangin; Xiao-Tong Song; Xiao-Tang Ju; Si-Yi Liu; Ju-Pei Shen; Hong-jie Di; Li-Li Han; Li-Mei Zhang (Journal of Environmental Management, 2024)

What are exposure biomarkers of rare earth elements for the ionic rare earth occupational population? - Qingfeng Chen; Jun Hong; Guowen Lai; Xiaobo Yang; Guoliang Chen; Na Xu; Xuewei Li; Kaibo Hu; Tianci Chen; Yang Song; Yinhua Wan (Environmental Pollution, 2024)

Covalently linked MOF@COF direct Z-scheme heterojunction for visible light-driven photocatalytic degradation of flotation agents - Hong-Xia Zhang; Sheng-Hua Ma; Hai-Xian Wang; Shao-Cong Li; Hai-Yun Shen; De-Ming Kong; Feng-Ying Wang; Li-Na Zhu (Journal of Environmental Chemical Engineering, 2024)

Performance of green solvents in microwave-assisted pretreatment of lignocellulose - Na Wang; Anran Xu; Kai Liu; Zhenyu Zhao; Hong Li; Xin Gao (Chemical Engineering Journal, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

The source of rock moisture in a sandstone cave in arid northern China: rainfall infiltration or vapor condensation? - Xiao-Wei Jiang; Kai-Gao Ouyang; Xu-Lin Tang; Shu-Cong Tan; Jia-Xin Shi; Na Li; Hong-Bin Yan; Jian-Guang Ren; Li Wan (Hydrogeology Journal, 2024)

O-acetyl-homoserine sulfhydrylase deficient Streptococcus suis serotype 2 strain SC19 becomes an avirulent strain and provides immune protection against homotype infection in mice - Tong Wu; Hexiang Jiang; Fengyang Li; Xuan Jiang; Jun Wang; Shaopeng Wei; Yi Sun; Yanyan Tian; Hong Chu; Yu Shi; Nan Zhang; Na Li; et al. (Veterinary Microbiology, 2024)

Monolithic melamine foam@COF composite: Preparation, characterization and applications in ultrafast removal and on-site quick assessment of Cd2+ pollution - Wei Li; Yue-Lei Hao; Wei-Liang Jin; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; Hong-Xin Jiang; De-Ming Kong (Journal of Cleaner Production, 2024)

Synthesis of an autochthonous microbial community by analyzing the core microorganisms responsible for the critical flavor of bran vinegar - Li Li; Na Li; Junjie Fu; Jun Liu; Xue Ping Wen; Hong Cao; Hongwei Xu; Ying Zhang; Rong Cao (Food Research International, 2024)

Exercise training inhibits macrophage-derived IL-17A-CXCL5-CXCR2 inflammatory axis to attenuate pulmonary fibrosis in mice exposed to silica - Fuyu Jin; Yaqian Li; Xuemin Gao; Xinyu Yang; Tian Li; Shupeng Liu; Zhongqiu Wei; Shifeng Li; Na Mao; Heliang Liu; Wenchen Cai; Hong Xu; et al. (Science of The Total Environment, 2023)

A co-twin control study of in utero exposure to poly- and perfluoroalkyl substances and associations with neonatal thyroid-stimulating hormone - Liqin Hu; Hong Mei; Xiaonan Cai; Feiyan Xiang; Na Li; Zhen Huang; Zhengrong Duan; Pan Yang; Han Xiao (Environmental Research, 2023)

Seismic performance of prefabricated replaceable graded-yielding energy-dissipating connectors - Fangyu Li; Yongfeng Du; Na Hong; Hu Li; Peihong Chi (Engineering Structures, 2023)

Prevalence of paratuberculosis in cattle in China: A systematic review and meta-analysis - Na Lu; Ya-Ling Niu; Yang Song; Dan-Dan Zhang; Jing Jiang; Jiaqi Wei; Hong-Li Geng; Hongwei Cao (Preventive Veterinary Medicine, 2023)

Ecytonucleospora hepatopenaei n. gen. et comb. (Microsporidia: Enterocytozoonidae): A redescription of the Enterocytozoon hepatopenaei (Tourtip et al., 2009), a microsporidian infecting the widely cultivated shrimp Penaeus vannamei - Yuan Wang; Jie Chen; Ying Na; Xin-cang Li; Jun-fang Zhou; Wen-hong Fang; Hong-xin Tan (Journal of Invertebrate Pathology, 2023)

T4PPVB-COP composite-driven innovative electrochemiluminescence aptasensor for ultra-sensitive detection of chlorpyrifos - Yanping Li; Qiong Hu; Jihui Zhang; Hong Zhou; Na Wang; Yishan Fang; Bo Cui (Food Chemistry, 2023)

Analysis of the spatial-temporal evolution of Green and low carbon utilization efficiency of agricultural land in China and its influencing factors under the goal of carbon neutralization - Jun Fu; Rui Ding; Yu-qi Zhu; Lin-yu Du; Si-wei Shen; Li-na Peng; Jian Zou; Yu-xuan Hong; Juan Liang; Ke-xin Wang; Wen-qian Xiao (Environmental Research, 2023)

Simultaneous extraction of C3H8 and C2H6 from ternary C3H8/C2H6/CH4 mixtures in an ultra-microporous metal–organic framework - Lan Lan; Nan Lu; Jia-Cheng Yin; Qiang Gao; Feifan Lang; Ying-Hui Zhang; Hong-Xiang Nie; Na Li; Xian-He Bu (Chemical Engineering Journal, 2023)

Leopard predation on wild Sichuan snub-nosed monkeys - Bin Yang; James R. Anderson; Ni-Na Gou; Jun Luo; Bo Hong; Wei-Wei Fu; Yong-Feng Chen; Wei-Feng Wang; Bao-Jia Cao; Shi-Yu Chen; Kai-Feng Wang; Bao-Guo Li (Primates, 2023)

Intermittent fasting and Alzheimer's disease—Targeting ketone bodies as a potential strategy for brain energy rescue - Yu- Cai Ye; Shi-Fan Chai; Xin-Ru Li; Mei-Na Wu; Hong-Yan Cai; Zhao-Jun Wang (Metabolic Brain Disease, 2023)

Observed and projected changes in wet and dry spells for the major river basins in East Asia - Lirong Huang; Haibo Du; Yongcai Dang; Hong S. He; Lei Wang; Risu Na; Na Li; Zhengfang Wu (International Journal of Climatology, 2023)
Spatiotemporal changes in wet and dry spells had significantly contributed to climate‐related natural hazards in East Asia, especially in river basins undergoing warming. However, few studies have systematically analysed these changes for river basins at different latitudes. Herein, we investigated the observed and projected variations in wet and dry spells for East Asian river basins at different latitudes. We found that river basins at low latitudes (Yangtze and Pearl rivers) had obvious wet characteristics, whereas those at high latitudes (Amur and Yellow rivers) had obvious dry characteristics. In general, the river basins presented a ‘wet south but dry north’ spatial pattern. Long‐duration wet spells have been shown to be the primary contributor to total wet spells in low‐latitude river basins, while long‐duration dry spells have been found to be the primary contributor to total dry spells in high‐latitude river basins. Importantly, climate is changing from prolonged wet spells to short, intense wet spells in low‐latitude river basins, whereas the climate is changing from single, short dry spells to moderate, prolonged dry spells at high latitudes. These changes indicate a high probability of flash floods in river basins at low latitudes and a high probability of droughts at high latitudes. In the future, more temporally clustered heavy precipitation events and prolonged dry spells may lead to increasingly uneven precipitation in high‐latitude river basins and the Pearl River basin, especially under the higher shared socioeconomic pathway scenarios. In contrast, more frequent consecutive heavy precipitation events may aggravate the risk of flooding in the Yangtze River basin. These findings are expected to serve as a guide for flood and drought risk mitigation in East Asia under a warming climate.

Effect of environmental factors on expression of staphylococcal enterotoxin genes - Hong-na Li; Zhao-di Kang; Tao Wang; Tao Li; Yan-ge Yang; Wei-e Zhou; Fei Yuan (Environmental Science and Pollution Research, 2023)

Tigliane-and daphnane-type diterpenoids from the buds of Daphne genkwa with their cytotoxic activities - Ying Chen; Cai-Lin Zhao; Wei Dong; Fei-Fan Song; Li-Na Guo; Hong-Lian Zhang; Lv Zhen; Li Li; Jin Ye; Bo Song (Natural Product Research, 2023)

Are the accessibility and facility environment of parks associated with mental health? A comparative analysis based on residential areas and workplaces - Hong Li; Na Ta; Bailang Yu; Jiayu Wu (Landscape and Urban Planning, 2023)

New α-pyrone and unsaturated ketone analogues from the endophytic fungus Lasiodiplodia sp. and their cytotoxic effects - Wei Dong; Wen-Bin Gao; Fan-Wei Liu; Jin-Ye; Ying Chen; Hong-Lian Zhang; Zhen Lv; Li-Na Guo; Bo Song (Phytochemistry Letters, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Expression profiles and bioinformatic analysis of microRNAs in myocardium of diabetic cardiomyopathy mice - Ting Wang; Lingling Yuan; Yanxia Chen; Jing Wang; Na Li; Hong Zhou (Genes & Genomics, 2023)

Immune functions of the Dscam extracellular variable region in Chinese mitten crab - Xiao-Li Zhang; Guo-Qing Shen; Xiao-Na Zhang; Yue-Hong Zhao; Wei-Wei Li; Qun Wang (Fish & Shellfish Immunology, 2023)

Effects of Fe(II) and organic carbon on nitrate reduction in surficial sediments of a large shallow freshwater lake - Na Li; Yong Li; Ruitao Lou; Hong Xu; Laraib Saeed (Journal of Environmental Management, 2023)

Effects of sericin on oxidative stress and PI3K/AKT/mTOR signal pathway in cryopreserved mice ovarian tissue - Wei Han Shu; Song He Yang; Meng Wei; Xiao Chao Liu; Zi Xuan Chen; Chen Yang Wei; Xin Zhang; Li Na Si; Zhi Hong Chen; Yue Bing Qiao; Dong Mei Li; Tie Cheng Sun; et al. (Cryobiology, 2023)

Seasonal spermatogenesis in the red-eared slider (Trachemys scripta elegans): The roles of GnRH, actin cytoskeleton, and MAPK - Na Li; Wenzhuo Rao; Shiyu Dai; Muhammad Shahid Iqbal; Haitao Shi; Li Ding; Meiling Hong (Animal Reproduction Science, 2023)

Deyeuxia angustifolia upward migration and nitrogen deposition change soil microbial community structure in an alpine tundra - Na Li; Haibo Du; Mai-He Li; Risu Na; Renkai Dong; Hong S. He; Shengwei Zong; Lirong Huang; Zhengfang Wu (Soil Biology and Biochemistry, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

FTO-Nrf2 axis regulates bisphenol F-induced leydig cell toxicity in an m6A-YTHDF2-dependent manner - Shi-meng Zhou; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Wen-bo Yuan; Yu Shi; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

Ultralight, robust, and high Prussian blue-loading polyacrylonitrile aerogel: Preparation, characterization and efficient adsorption/removal of Cs+ - Xiao-Bo Yang; Wei Li; Ze-Zhong Lin; Jing-Qi Liu; Hong-Xin Jiang; Hao Jia; Wei-Liang Jin; Xin-Long Hou; Bing-Xuan Du; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

A general way to manipulate electrical conductivity of graphene - Liqing Chen; Nian Li; Xinling Yu; Shudong Zhang; Cui Liu; Yanping Song; Zhao Li; Shuai Han; Wenbo Wang; Pengzhan Yang; Na Hong; Sarmad Ali; et al. (Chemical Engineering Journal, 2023)

[Cuproptosis-related immune gene signature predicts clinical benefits from anti-PD-1/PD-L1 therapy in non-small-cell lung cancer - Linfeng Luo; Anlin Li; Sha Fu; Wei Du; Li-Na He; Xuanye Zhang; Yixing Wang; Yixin Zhou; Yang Yunpeng; Zhang Li; Shaodong Hong (Immunologic Research, 2023)

A novel Halbach array electromagnetic pump for liquid metal flow: Design proposal and performance analysis - Liang Yao; Xiao-Bin Li; Hong-Na Zhang; Li-Xia Chen; Feng-Chen Li (Annals of Nuclear Energy, 2023)

A 13 million-year record of Li isotope compositions in island carbonates: Constraints on bulk inorganic carbonate as a global seawater Li isotope archive - Guang-Yi Wei; Feifei Zhang; Yi-Sheng Yin; Yi-Bo Lin; Philip A.E. Pogge von Strandmann; Mengchun Cao; Na Li; Guolin Xiong; Xinran Chen; Caiwei Fan; Changgui Xu; Fei Tan; et al. (Geochimica et Cosmochimica Acta, 2023)

RNA binding protein YTHDF1 mediates bisphenol S-induced Leydig cell damage by regulating the mitochondrial pathway of BCL2 and the expression of CDK2-CyclinE1 - Jing-zhi Li; Shi-meng Zhou; Wen-bo Yuan; Hong-qiang Chen; Yong Zeng; Jun Fan; Zhe Zhang; Na Wang; Jia Cao; Wen-bin Liu (Environmental Pollution, 2023)

The real-time detection of acupuncture-induced extracellular ATP mobilization in acupoints and exploration of its role in acupuncture analgesia - Wei-Min Zuo; Yu-Jia Li; Kai-Yu Cui; Dan Shen; Di Zhang; Ya-Wen Zheng; Meng Huang; Yong Wu; Xue-Yong Shen; Li-Na Wang; Guang-Hong Ding (Purinergic Signalling, 2023)

IFI44L as a novel epigenetic silencing tumor suppressor promotes apoptosis through JAK/STAT1 pathway during lung carcinogenesis - Yong Zeng; Hong-qiang Chen; Zhe Zhang; Jun Fan; Jing-zhi Li; Shi-meng Zhou; Na Wang; Su-peng Yan; Jia Cao; Jin-yi Liu; Zi-yuan Zhou; Wen-bin Liu (Environmental Pollution, 2023)

A Review and Perspective of Environmental Disinfection Technology Based on Microwave Irradiation - Liming Liu; Na Wang; Azhar Ali Laghari; Hong Li; Can Wang; Zhenyu Zhao; Xin Gao; Qiang Zeng (Current Pollution Reports, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

TET1 involved in bisphenol A induced TM3 Leydig cell toxicity by regulating Cav3.3 hydroxymethylation - Shi-meng Zhou; Wen-bo Yuan; Jing-zhi Li; Hong-qiang Chen; Yong Zeng; Na Wang; Jun Fan; Zhe Zhang; Yuanyuan Xu; Jia Cao; Wen-bin Liu (Chemosphere, 2023)

An integrative analysis of lncRNAs and mRNAs highlights the potential roles of lncRNAs in the process of follicle selection in Taihang chickens - Bei-Bei Zhang; Meng-Xiao Li; Hong-Na Wang; Chao Liu; Yan-Yan Sun; Teng-He Ma (Theriogenology, 2023)

Impact of air pollutants on influenza-like illness outpatient visits under urbanization process in the sub-center of Beijing, China - Zhong-Song Zhang; Lu Xi; Li-Li Yang; Xin-Yao Lian; Juan Du; Yan Cui; Hong-Jun Li; Wan-Xue Zhang; Chao Wang; Bei Liu; Yan-Na Yang; Fuqiang Cui; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effect of ammonia stress on AMPK regulating-carbohydrate and lipid metabolism in Chinese striped-neck turtle (Mauremys sinensis) - Ijaz Khan; Yingnan Lu; Na Li; Haitao Shi; Li Ding; Meiling Hong; Zhenhua Fang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Facile fabrication of hierarchically porous melamine foam@COF composite for sample treatment of non-targeted food safety analysis and oil/water separation - Wei Li; Wei-Liang Jin; Hong-Xin Jiang; Rui Wang; Hao Jia; Jing-Qi Liu; An-Na Tang; Li-Na Zhu; De-Ming Kong (Chemical Engineering Journal, 2023)

Efficient H2 production in a novel separator electrode assembly (SEA) microbial electrolysis cell - Na Zhao; Dawei Liang; Hong Liu; Shujuan Meng; Xiaohu Li (Chemical Engineering Journal, 2023)

Chronological deposition record of trace metals in sediment cores from Chaohu Lake, Anhui Province, China - Xin Wang; Na Gao; Yangyang Liang; Fei Liu; Xiuping Hong; Xiujie Zhou; Liqiang Sun; Hui Li; Ting Fang (Environmental Monitoring and Assessment, 2022)

Can collaborative innovation constrain ecological footprint? Empirical evidence from Guangdong-Hong Kong-Macao Greater Bay Area, China - Xiaojun You; Qixiang Li; Kyle M. Monahan; Fei Fan; Haiqian Ke; Na Hong (Environmental Science and Pollution Research, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Influence of joint angle on the instability failure characteristics and AE evolution law of underground caverns - Xiao Wang; Na Wu; Hong Li; Yatao Yan (European Journal of Environmental and Civil Engineering, 2022)

Identification and functional characterization of safflower cysteine protease 1 as negative regulator in response to low-temperature stress in transgenic Arabidopsis - Hong Yingqi; Yanxi Lv; Jianyi Zhang; Naveed Ahmad; Youbao Li; Nan Wang; Liu Xiuming; Yao Na; Xiaokun Li (Planta, 2022)

Characterization and Cys-directed mutagenesis of urate oxidase from Bacillus subtilis BS04 - Tong-tong Zhu; Hong-na Chen; Lei Yang; Ying-bao Liu; Wei Li; Wen-xiu Sun (Biologia, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

Deubiquitylation and stabilization of Acf7 by ubiquitin carboxyl-terminal hydrolase 14 (USP14) is critical for NSCLC migration - Guobei Yan; Na Liu; Junhua Wang; Jun Tian; Hongbin Liu; Suping Li; Wenchao Liu; Xiaoliang Li; Kai Li; Hong Wang (Journal of Biosciences, 2021)

Design, synthesis, brine shrimp lethality and cytotoxicity of some novel 17a-aza-D-homo-androster-17-one derivatives - Dongfeng Hong; Yiming Ma; Siyao Song; Na Li; Junru Wang (Natural Product Research, 2021)

1,4-Dioxane Degradation Performance of Tetrahydrofuran-Grown Arthrobacter sp. WN18 - Peng Wang; Tingchen Cui; Jialu Li; Na Liu; Mei Hong (Water, Air, & Soil Pollution, 2021)

Study of the mechanical performance of excavation under asymmetrical pressure and reinforcement measures - Wenchao Zhang; Na Wu; Pengjiao Jia; Xiaoqi Zhou; Hong Li; Guoguang Wang (Arabian Journal of Geosciences, 2021)

Chronic stress promotes acute myeloid leukemia progression through HMGB1/NLRP3/IL-1β signaling pathway - Na Liu; Yifan Wu; Xin Wen; Peng Li; Fei Lu; Hong Shang (Journal of Molecular Medicine, 2021)

Cytokinins as central regulators during plant growth and stress response - Si-Min Li; Hong-Xiang Zheng; Xian-Sheng Zhang; Na Sui (Plant Cell Reports, 2021)

Phytochemical and antitumor studies on Cynanchum mongolicum (Maxim.) Kom - Yong-Cheng Yang; Yan-Ming Wang; Zi-Jian Rong; Li-Na Hong; Qian Zhang; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2020)

Spatio-Temporal Variations in the Abundance and Community Structure of Nitrospira in a Tropical Bay - Tie-Qiang Mao; Yan-Qun Li; Hong-Po Dong; Wen-Na Yang; Li-Jun Hou (Current Microbiology, 2020)

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Trace elements determination and health risk assessment of Tricholoma matsutake from Yunnan Province, China - Hong-xian Chen; Yun Chen; Songfei Li; Wei Zhang; Ying Zhang; Shan Gao; Na Li; Lei Tao; Ying Wang (Journal of Consumer Protection and Food Safety, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

Multicenter-Based Population Pharmacokinetic Analysis of Ciclosporin in Hematopoietic Stem Cell Transplantation Patients - Ling Xue; Wen-juan Zhang; Ji-xin Tian; Lin-na Liu; Hai-hong Yan; Wen-wen Zhang; Xiao-liang Ding; Jing-jing Zhang; Li-yan Miao (Pharmaceutical Research, 2020)

Risks of maternal prepregnancy overweight/obesity, excessive gestational weight gain, and bottle-feeding in infancy rapid weight gain: evidence from a cohort study in China - Shaoping Yang; Hong Mei; Hui Mei; Yan Yang; Na Li; Yafei Tan; Yiming Zhang; Dan Zhang; Yan Zhang; An’na Peng; Bin Zhang (Science China Life Sciences, 2019)

Formation mechanism and mixing behavior of Nanyang thermal spring, Xingshan County of Hubei Province, central China - Na Li; Hong Zhou; Zhang Wen; Hamza Jakada (Hydrogeology Journal, 2019)

Stress-dependent anisotropy index of strength and deformability of jointed rock mass: insights from a numerical study - Na Wu; Zheng-zhao Liang; Ying-chun Li; Hong Li; Wan-run Li; Mei-li Zhang (Bulletin of Engineering Geology and the Environment, 2019)

Numerical Study on Anisotropy of the Representative Elementary Volume of Strength and Deformability of Jointed Rock Masses - Zhengzhao Liang; Na Wu; Yingchun Li; Hong Li; Wanrun Li (Rock Mechanics and Rock Engineering, 2019)

Fn14 Participates in Neuropathic Pain Through NF-κB Pathway in Primary Sensory Neurons - Li-Na Huang; Yun Zou; Shao-Gen Wu; Hong-Hong Zhang; Qing-Xiang Mao; Jin-Bao Li; Yuan-Xiang Tao (Molecular Neurobiology, 2019)

Joint toxicity of six common heavy metals to Chlorella pyrenoidosa - Ling-Yun Mo; Dan-Na Zhao; Meng Qin; Li-Tang Qin; Hong-Hu Zeng; Yan-Peng Liang (Environmental Science and Pollution Research, 2019)

Physiological and biochemical responses of Dunaliella salina exposed to acrylamide - Na Ling; Hong-Xiu Li; Hong-Shi Guo; Xiu-Ming Cao; Xiao-Rui Liu (Biologia, 2019)

Synergistic deletion of RGS1 and COS1 may reduce the pathogenicity of Magnaporthe oryzae - He Na; An Bang; Xie Qing-biao; Yan Xia; Feng Hui-min; Luo Hong-li; He Chao-zu (Archives of Microbiology, 2019)

Preparation of pickling-reheating activated alfalfa biochar with high adsorption efficiency for p-nitrophenol: characterization, adsorption behavior, and mechanism - Hong Chen; Yuting Zhang; Jialu Li; Pengpeng Zhang; Na Liu (Environmental Science and Pollution Research, 2019)

Impact of surfactant and dissolved organic matter on uptake of atrazine in maize and its mobility in soil - Bing Bing Tian; Jing Hua Zhou; Fei Xie; Qian Nan Guo; Ai Ping Zhang; Xin Qiang Wang; Qian Qian Yu; Na Li; Hong Yang (Journal of Soils and Sediments, 2019)

Sex Differences in Neuropathology and Cognitive Behavior in APP/PS1/tau Triple-Transgenic Mouse Model of Alzheimer’s Disease - Jun-Ting Yang; Zhao-Jun Wang; Hong-Yan Cai; Li Yuan; Meng-Ming Hu; Mei-Na Wu; Jin-Shun Qi (Neuroscience Bulletin, 2018)

Flavonoids of Rosa roxburghii Tratt offers protection against radiation induced apoptosis and inflammation in mouse thymus - Sai-Juan Xu; Fan Zhang; Li-Juan Wang; Ming-Hua Hao; Xian-jun Yang; Na-na Li; Hong-long Ji; Ping Xu (Apoptosis, 2018)

Alterations of ATP-sensitive K+ channels in human umbilical arterial smooth muscle during gestational diabetes mellitus - Hongliang Li; Sung Eun Shin; Mi Seon Seo; Jin Ryeol An; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Jeeyoung Kim; Mi-Jin Yim; Jeong Min Lee; Tae Gyu An; Jihan Jeon; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

HNMDA: heterogeneous network-based miRNA–disease association prediction - Li-Hong Peng; Chuan-Neng Sun; Na-Na Guan; Jian-Qiang Li; Xing Chen (Molecular Genetics and Genomics, 2018)

Conflicting meal recommendations for oral oncology drugs: pose risks to patient care? - Guo Yu; Dan-Na Wu; Yan Gong; Guo-Fu Li; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2018)

Inhibition of the Voltage-Dependent K+ Current by the Tricyclic Antidepressant Desipramine in Rabbit Coronary Arterial Smooth Muscle Cells - Sung Eun Shin; Hongliang Li; Jin Ryeol An; Mi Seon Seo; Sung Hun Na; Won-Kyo Jung; Amy L. Firth; Kwon-Soo Ha; Eun-Taek Han; Seok-Ho Hong; Il-Whan Choi; Won Sun Park (Cardiovascular Toxicology, 2018)

Early diagnosis of acute kidney injury in aged patients undergoing percutaneous coronary intervention - Hong-hua Ye; Gen Shen; Qun Luo; Fang-fang Zhou; Xiao-ling Xie; Chun-yan Wang; Li-na Han (Journal of Zhejiang University-SCIENCE B, 2018)

Establishment and characterization of a kidney cell line from kelp grouper Epinephelus moara - Xiao-Feng Liu; Ya-Hong Wu; Shi-Na Wei; Na Wang; Peng-Fei Li; Yang-Zhen Li; Nian-Wei Zhang; Qi-Wei Qin; Song-Lin Chen (Fish Physiology and Biochemistry, 2018)

A catastrophe progression approach based index sensitivity analysis model for the multivariate flooding process - Li-Na Wang; Xiao-Hong Chen; Yong-Xin Xu; Ming-Zhi Huang (Stochastic Environmental Research and Risk Assessment, 2018)

First evidence of pyrrolizidine alkaloid N-oxide-induced hepatic sinusoidal obstruction syndrome in humans - Mengbi Yang; Jianqing Ruan; Hong Gao; Na Li; Jiang Ma; Junyi Xue; Yang Ye; Peter Pi-Cheng Fu; Jiyao Wang; Ge Lin (Archives of Toxicology, 2017)

Ion Channel Genes and Epilepsy: Functional Alteration, Pathogenic Potential, and Mechanism of Epilepsy - Feng Wei; Li-Min Yan; Tao Su; Na He; Zhi-Jian Lin; Jie Wang; Yi-Wu Shi; Yong-Hong Yi; Wei-Ping Liao (Neuroscience Bulletin, 2017)

Biosynthesis of staphylococcal enterotoxin A by genetic engineering technology and determination of staphylococcal enterotoxin A in water by HPLC-ESI-TOF - Hong-na Li; Fei Yuan; Yun-jing Luo; Jian-feng Wang; Chuan-bin Zhang; Wei-e Zhou; Zhi-qin Ren; Wen-jie Wu; Feng Zhang (Environmental Science and Pollution Research, 2017)

Isolation of Viable but Non-culturable Bacteria from Printing and Dyeing Wastewater Bioreactor Based on Resuscitation Promoting Factor - Yi Jin; Guojuan Gan; Xiaoyun Yu; Dongdong Wu; Li Zhang; Na Yang; Jiadan Hu; Zhiheng Liu; Lixin Zhang; Huachang Hong; Xiaoqing Yan; Yan Liang; et al. (Current Microbiology, 2017)

Transcriptional sequencing and analysis of major genes involved in the adventitious root formation of mango cotyledon segments - Yun-He Li; Hong-Na Zhang; Qing-Song Wu; Gloria K. Muday (Planta, 2017)

The species of Lentaria (Gomphales, Basidiomycota) from China based on morphological and molecular evidence - Li-Na Liu; Ling Wu; Zuo-Hong Chen; Tolgor Bau; Ping Zhang (Mycological Progress, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Epigenetic Downregulation of Scn3a Expression by Valproate: a Possible Role in Its Anticonvulsant Activity - Na-Na Tan; Hui-Ling Tang; Guo-Wang Lin; Yong-Hong Chen; Ping Lu; Hai-Jun Li; Mei-Mei Gao; Qi-Hua Zhao; Yong-Hong Yi; Wei-Ping Liao; Yue-Sheng Long (Molecular Neurobiology, 2017)

Novel compound heterozygous mutations in ZAP70 in a Chinese patient with leaky severe combined immunodeficiency disorder - Qing Liu; Yan-Ping Wang; Qiao Liu; Qin Zhao; Xue-Mei Chen; Xiu-Hong Xue; Li-Na Zhou; Yuan Ding; Xue-Mei Tang; Xiao-Dong Zhao; Zhi-Yong Zhang (Immunogenetics, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

A new piperidine alkaloid from the leaves of Microcos paniculata L. - Gang Zhang; Na Zhang; Li Xu; Hong-Tan Wu; Dan Chen; Qi-Huang Lin; Lian-Zhong Luo (Natural Product Research, 2017)

Characterization of the whole chloroplast genome of Caragana microphylla Lam (Fabaceae) - Bing-bing Liu; Na Duan; Hong-li Zhang; Shuang Liu; Jian-wei Shi; Bao-feng Chai (Conservation Genetics Resources, 2016)

Research progress of the role and mechanism of extracellular signal-regulated protein kinase 5 (ERK5) pathway in pathological pain - Li-na Yu; Li-hong Sun; Min Wang; Min Yan (Journal of Zhejiang University-SCIENCE B, 2016)

Effects of yeast products on the intestinal morphology, barrier function, cytokine expression, and antioxidant system of weaned piglets - Huan-sheng Yang; Fei Wu; Li-na Long; Tie-jun Li; Xia Xiong; Peng Liao; Hong-nan Liu; Yu-long Yin (Journal of Zhejiang University-SCIENCE B, 2016)

CGRP 8-37 enhances lipopolysaccharide-induced acute lung injury and regulating aquaporin 1 and 5 expressions in rats - Fu Hong-min; Huangfu Chun-rong; Zheng Rui; Su Li-na; Wang Ya-jun; Li Li (Journal of Physiology and Biochemistry, 2016)

Myricetin protects against diet-induced obesity and ameliorates oxidative stress in C57BL/6 mice - Hong-ming Su; Li-na Feng; Xiao-dong Zheng; Wei Chen (Journal of Zhejiang University-SCIENCE B, 2016)

Genome-wide association mapping of glyphosate-resistance in Gossypium hirsutum races - Yuan-Yuan Wang; Zhong-Li Zhou; Xing-Xing Wang; Xiao-Yan Cai; Xiao-Na Li; Chun-Ying Wang; Yu-Hong Wang; Liu Fang; Kun-Bo Wang (Euphytica, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Molecular cloning of HMW glutenin subunits from Roegneria kamoji (Poaceae: Triticeae) - Ying-Xia Lei; Kuai Yu; Yi Wang; Xing Fan; Hou-Yang Kang; Li-Na Sha; Yong-Hong Zhou; Hai-Qin Zhang (Biologia, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Transcriptome sequencing discovers genes related to fatty acid biosynthesis in the seeds of Eucommia ulmoides - Yan-zhi Feng; Lu Wang; Jian-min Fu; Ta-na Wuyun; Hong-yan Du; Xiao-feng Tan; Feng Zou; Fang-dong Li (Genes & Genomics, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The SIRT1 inhibitor, nicotinamide, inhibits hepatitis B virus replication in vitro and in vivo - Wan-Yu Li; Ji-Hua Ren; Na-Na Tao; Long-Kuan Ran; Xiang Chen; Hong-Zhong Zhou; Bo Liu; Xiao-Song Li; Ai-Long Huang; Juan Chen (Archives of Virology, 2016)

Radix ranunculus temate saponins induces apoptosis via the death receptor and mitochondrial pathways in SGC-7901 cells - Mao-lin Li; Han-min Gu; Hong-ya Hang; Yao-li Jiang; Jiao Jiang; Qian-na Gu; Wen-yan Wu (Molecular & Cellular Toxicology, 2015)

HPLC simultaneous determination of arbutin, chlorogenic acid and 6′- O -caffeoylarbutin in different parts of Vaccinium dunalianum Wight - Xu-Lu Luo; Na Li; Min Xu; Hong-Tao Zhu; Peng He; Yong Ding; Ping Zhao; Ying-Jun Zhang (Natural Product Research, 2015)

Identification of insecticidal constituents of the essential oils of Dahlia pinnata Cav. against Sitophilus zeamais and Sitophilus oryzae - Da-Cheng Wang; Da-Ren Qiu; Li-Na Shi; Hong-Yu Pan; Ya-Wei Li; Jin-Zhu Sun; Ying-Jie Xue; Dong-Sheng Wei; Xiang Li; Ya-Mei Zhang; Jian-Chun Qin (Natural Product Research, 2015)

Development of a test strip for rapid detection of lactoperoxidase in raw milk - Hong-xia Che; Bo Tian; Li-na Bai; Li-ming Cheng; Li-li Liu; Xiao-na Zhang; Zhan-mei Jiang; Xiao-xi Xu (Journal of Zhejiang University-SCIENCE B, 2015)

Dissipation and Degradation Dynamics of Thifluzamide in Rice Field - Li Na Wei; Ping Wu; Fu Rong Wang; Hong Yang (Water, Air, & Soil Pollution, 2015)

Activation of NOD1 by DAP contributes to myocardial ischemia/reperfusion injury via multiple signaling pathways - Hui Yang; Nan Li; Li-Na Song; Lei Wang; Cui Tian; Chao-Shu Tang; Jie Du; Hui-Hua Li; Xiao-Hong Yu; Hong-Xia Wang (Apoptosis, 2015)

Novel Pyridinium Inner Salt Dye and its Complexes: Synthesis, Crystal Structures and Photophysical Properties - Yong-Hong Zhou; Na-Li Wang; Ti-Fang Miao; Juan-Gang Wang; Zhe-Yu Wang (Journal of Fluorescence, 2015)

Morphological changes in gray matter volume correlate with catechol-O-methyl transferase gene Val158Met polymorphism in first-episode treatment-naïve patients with schizophrenia - Ming-Li Li; Bo Xiang; Yin-Fei Li; Xun Hu; Qiang Wang; Wan-Jun Guo; Wei Lei; Chao-Hua Huang; Lian-Sheng Zhao; Na Li; Hong-Yan Ren; Hui-Yao Wang; et al. (Neuroscience Bulletin, 2015)

Design and applications of bifunctional cinnamide derivatives as potential antimycobacterial agents with few hepatotoxic effects - Zheng-Rong Wu; De-Juan Zhi; Li-Fang Zheng; Jian-Ying Li; Yang Li; Qing-Jian Xie; Na Feng; Yan-Fang Bao; Qi-Yu Gao; Ying Song; Hong-Yu Li (Medicinal Chemistry Research, 2015)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

Promoter hypermethylation may be an important mechanism of the transcriptional inactivation of ARRDC3, GATA5, and ELP3 in invasive ductal breast carcinoma - Da Wang; Peng-Na Yang; Jin Chen; Xian-Yao Zhou; Qiu-Jun Liu; Hong-Jiang Li; Chang-Long Li (Molecular and Cellular Biochemistry, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Erratum to: Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

Overexpression of Human E46K Mutant α-Synuclein Impairs Macroautophagy via Inactivation of JNK1-Bcl-2 Pathway - Jia-Qing Yan; Yu-He Yuan; Yan-Na Gao; Ju-Yang Huang; Kai-Li Ma; Yan Gao; Wan-Qing Zhang; Xiao-Feng Guo; Nai-Hong Chen (Molecular Neurobiology, 2014)

A novel method for the rapid detection of benzo(a)pyrene in liquid milk by dimethyl sulfoxide selectively enhanced synchronous fluorescence spectrometry - Li-Rong Lin; He-Dong Luo; Xiu-Ying Li; Na Li; Na Zhou; Yu-Zhu Jia; Yi-Hong Liu; Yao-Qun Li (Food Additives & Contaminants: Part A, 2014)

HER-2 overexpression and survival in colorectal cancer: a meta-analysis - Chao Li; Da-ren Liu; Long-yun Ye; Ling-na Huang; Sanjay Jaiswal; Xiao-wen Li; Hou-hong Wang; Li Chen (Journal of Zhejiang University-SCIENCE B, 2014)

M3 mAChR-mediated IL-8 expression through PKC/NF-κB signaling pathways - Zu-Peng Xu; Yun Song; Kai Yang; Wei Zhou; Li-Na Hou; Liang Zhu; Hong-Zhuan Chen; Yong-Yao Cui (Inflammation Research, 2014)

Prevalence of human papillomavirus infection in esophageal and cervical cancers in the high incidence area for the two diseases from 2007 to 2009 in Linzhou of Henan Province, Northern China - Hong Yan Liu; Sheng Li Zhou; Jian Wei Ku; Dong Yun Zhang; Bei Li; Xue Na Han; Zong Min Fan; Ji Li Cui; Hong Li Lin; Er Tao Guo; Xi Chen; Yuan Yuan; et al. (Archives of Virology, 2014)

Identification of Conserved and Novel Cold-Responsive MicroRNAs in Trifoliate Orange (Poncirus trifoliata (L.) Raf.) Using High-Throughput Sequencing - Xiao-Na Zhang; Xin Li; Ji-Hong Liu (Plant Molecular Biology Reporter, 2014)

Runoff characteristics of the Nen River Basin and its cause - Hong-yan Li; Yu-xin Wang; Li-na Jia; Ya-nan Wu; Miao Xie (Journal of Mountain Science, 2014)

Co-expression of the Arabidopsis SOS genes enhances salt tolerance in transgenic tall fescue (Festuca arundinacea Schreb.) - Dong-Mei Ma; Wei-Rong Xu; Hui-Wen Li; Feng-Xia Jin; Ling-Na Guo; Jing Wang; Hong-Jun Dai; Xing Xu (Protoplasma, 2014)

CD73+ adipose-derived mesenchymal stem cells possess higher potential to differentiate into cardiomyocytes in vitro - Qiong Li; Li-Jie Qi; Zhi-Kun Guo; He Li; Hong-Bo Zuo; Na-Na Li (Journal of Molecular Histology, 2013)

The detection of QTLs controlling bacterial wilt resistance in tobacco (N. tabacum L.) - Yi-liang Qian; Xin-sheng Wang; Da-zhou Wang; Li-na Zhang; Chao-long Zu; Zheng-liang Gao; Hong-jun Zhang; Zhi-yong Wang; Xue-yong Sun; Da-nian Yao (Euphytica, 2013)

The TRIMCyp genotype in four species of macaques in China - Chang-Qing Yu; Lei Na; Xiao-Ling Lv; Jian-Dong Liu; Xiao-Ming Liu; Fang Ji; Yong-Hui Zheng; Hong-Li Du; Xian-Gang Kong; Jian-Hua Zhou (Immunogenetics, 2013)

Synthesis, structure, and biological assay of cinnamic amides as potential EGFR kinase inhibitors - Mao Zhang; Xiang Lu; Hong-Jia Zhang; Na Li; Yu Xiao; Hai-Liang Zhu; Yong-Hao Ye (Medicinal Chemistry Research, 2013)

Surgical Trauma Induces Iron Accumulation and Oxidative Stress in a Rodent Model of Postoperative Cognitive Dysfunction - Li-Na An; Yang Yue; Wen-Zhi Guo; Yu-Liang Miao; Wei-Dong Mi; Hong Zhang; Zhi-Li Lei; Shu-Jun Han; Lan Dong (Biological Trace Element Research, 2013)

Comparative transcriptome analysis of tobacco (Nicotiana tabacum) leaves to identify aroma compound-related genes expressed in different cultivated regions - Bo Lei; Xue-Hua Zhao; Kai Zhang; Jie Zhang; Wei Ren; Zhu Ren; Yi Chen; Hui-Na Zhao; Wen-Jie Pan; Wei Chen; Hong-Xun Li; Wen-Ya Deng; et al. (Molecular Biology Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Genetic polymorphisms of lipoprotein lipase gene and their associations with growth traits in Xiangxi cattle - Xing Ping Wang; Zhuo Ma Luoreng; Feng Li; Jin Ren Wang; Na Li; Shu Hong Li (Molecular Biology Reports, 2012)

Molecular and cytological evidences for the natural wheatgrass hybrids occurrence and origin in west China - Jian Zeng; Xing Fan; Hai-Qin Zhang; Li-Na Sha; Hou-Yang Kang; Li Zhang; Rui-Wu Yang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

An effective approach for land-cover classification from airborne lidar fused with co-registered data - Yang Cao; Hong Wei; Huijie Zhao; Na Li (International Journal of Remote Sensing, 2012)

Impairment of liver regeneration by the histone deacetylase inhibitor valproic acid in mice - Qi Ke; Rui-na Yang; Feng Ye; Yu-jia Wang; Qiong Wu; Li Li; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2012)

Tea consumption and risk of stroke: a dose-response meta-analysis of prospective studies - Li Shen; Liu-guang Song; Hong Ma; Chun-na Jin; Jian-an Wang; Mei-xiang Xiang (Journal of Zhejiang University-SCIENCE B, 2012)

Simultaneous Quantitative Analysis of Three Compounds Using Three-Dimensional Fluorescence Spectra Based on Digital Image Techniques - Hong Lin Zhai; Zhi Jie Shan; Rui Na Li; E Yu (Journal of Fluorescence, 2012)

Enhanced Anti-Diabetic Activity of a Combination of Chromium(III) Malate Complex and Propolis and its Acute Oral Toxicity Evaluation - Xiang-Yang Wu; Fang Li; Ting Zhao; Guang-Hua Mao; Jing Li; Hong-Yuan Qu; Yue-Na Ren; Liu-Qing Yang (Biological Trace Element Research, 2012)

Phylogeny and molecular evolution of the DMC1 gene within the StH genome species in Triticeae (Poaceae) - Xiao-Li Wang; Xing Fan; Jian Zeng; Li-Na Sha; Hai-Qin Zhang; Hou-Yang Kang; Rui-Wu Yang; Li Zhang; Chun-Bang Ding; Yong-Hong Zhou (Genes & Genomics, 2012)

Organ Histopathological Changes and its Function Damage in Mice Following Long-term Exposure to Lanthanides Chloride - Jie Cheng; Na Li; Jingwei Cai; Zhe Cheng; Renping Hu; Qian Zhang; Fangfang Wan; Qingqing Sun; Suxing Gui; Xuezi Sang; Ling Wang; Fashui Hong (Biological Trace Element Research, 2012)

Population Genetic Structure of the Endangered Brasenia schreberi in South Korea Based on Nuclear Ribosomal Spacer and Chloroplast DNA Sequences - Changkyun Kim; Jongduk Jung; Hye Ryun Na; Suk Weon Kim; Wei Li; Yasuro Kadono; Hyunchur Shin; Hong-Keun Choi (Journal of Plant Biology, 2012)

Determination of aflatoxins in edible oil from markets in Hebei Province of China by liquid chromatography–tandem mass spectrometry - Li-xin Yang; Yin-ping Liu; Hong Miao; Bin Dong; Na-jing Yang; Feng-qi Chang; Li-xue Yang; Jing-bo Sun (Food Additives & Contaminants Part B-Surveillance, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Osteoinduction by Ca-P biomaterials implanted into the muscles of mice - Rui-na Yang; Feng Ye; Li-jia Cheng; Jin-jing Wang; Xiao-feng Lu; Yu-jun Shi; Hong-song Fan; Xing-dong Zhang; Hong Bu (Journal of Zhejiang University-SCIENCE B, 2011)

Enhanced Gene Transduction into Skeletal Muscle of Mice In Vivo with Pluronic Block Copolymers and Ultrasound Exposure - Yun-Chao Chen; Li-Ping Jiang; Na-Xiang Liu; Lu Ding; Xiao-Ling Liu; Zhi-Hui Wang; Kai Hong; Qing-Ping Zhang (Cell Biochemistry and Biophysics, 2011)

Expression of a novel thermostable Cu, Zn-superoxide dismutase from Chaetomium thermophilum in Pichia pastoris and its antioxidant properties - Li-Qing Zhang; Fang-Xian Guo; Hong-Quan Xian; Xiu-Juan Wang; An-Na Li; Duo-Chuan Li (Biotechnology Letters, 2011)

The Mechanism of Liver Injury in Mice Caused by Lanthanoids - Min Fei; Na Li; Yuguan Ze; Jie Liu; Sisi Wang; Xiuaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

P38-Nrf-2 Signaling Pathway of Oxidative Stress in Mice Caused by Nanoparticulate TiO2 - Jue Wang; Na Li; Lei Zheng; Sisi Wang; Ying Wang; Xiaoyang Zhao; Yanmei Duan; Yaling Cui; Min Zhou; Jingwei Cai; Songjie Gong; Han Wang; et al. (Biological Trace Element Research, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Oxidative Stress in the Liver of Mice Caused by Intraperitoneal Injection with Lanthanoides - Min Fei; Na Li; Yuguan Ze; Jie Liu; Xiaolan Gong; Yanmei Duan; Xiaoyang Zhao; Han Wang; Fashui Hong (Biological Trace Element Research, 2011)

The functional expression of calcium-sensing receptor in the differentiated THP-1 cells - Yu-hui Xi; Hong-zhu Li; Wei-hua Zhang; Li-na Wang; Li Zhang; Yan Lin; Shu-zhi Bai; Hong-xia Li; Ling-yun Wu; Rui Wang; Chang-qing Xu (Molecular and Cellular Biochemistry, 2010)

Structural basis for the decrease in the outward potassium channel current induced by lanthanum - Li Hong Wang; Na Jiang; Bo Zhao; Xiao Dong Li; Tian Hong Lu; Xiao Lan Ding; Xiao Hua Huang (JBIC Journal of Biological Inorganic Chemistry, 2010)

β-catenin signaling involves HGF-enhanced HepG2 scattering through activating MMP-7 transcription - Fei-Yan Pan; Sheng-Zhou Zhang; Na Xu; Fan-Li Meng; Hong-Xia Zhang; Bin Xue; Xiao Han; Chao-Jun Li (Histochemistry and Cell Biology, 2010)

Effects of Manganese Deficiency on Spectral Characteristics and Oxygen Evolution in Maize Chloroplasts - Xiaolan Gong; Ying Wang; Chao Liu; Sisi Wang; Xiaoyang Zhao; Min Zhou; Na Li; Yun Lu; Fashui Hong (Biological Trace Element Research, 2010)

Interaction Between Nanoparticulate Anatase TiO2 and Lactate Dehydrogenase - Yanmei Duan; Na Li; Chao Liu; Huiting Liu; Yaling Cui; Han Wang; Fashui Hong (Biological Trace Element Research, 2010)

Genetic evolution of equine influenza viruses isolated in China - Ting Qi; Wei Guo; Wen-Qiang Huang; Hong-Mei Li; Li-Ping Zhao; Ling-Li Dai; Na He; Xiao-Fang Hao; Wen-Hua Xiang (Archives of Virology, 2010)

The Mechanism of CeCl3 on the Activiation of Alanine Aminotransferase from Mice - Na Li; Yanmei Duan; Chao Liu; Fashui Hong (Biological Trace Element Research, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

The Oxidative Damage in Lung of Mice Caused By Lanthanoide - Na Li; Sisi Wang; Jie Liu; Linglan Ma; Yanmei Duan; Fashui Hong (Biological Trace Element Research, 2010)

Species and distribution of rare earth elements in the Baotou section of the Yellow River in China - Jiang He; Chang-Wei Lü; Hong-Xi Xue; Ying Liang; Saruli Bai; Ying Sun; Li-Li Shen; Na Mi; Qing-Yun Fan (Environmental Geochemistry and Health, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Cerium Relieves the Inhibition of Nitrogen Metabolism of Spinach Caused by Magnesium Deficiency - Sitao Yin; Yuguan Ze; Chao Liu; Na Li; Min Zhou; Yanmei Duan; Fashui Hong (Biological Trace Element Research, 2009)

The Effects of Lanthanoid on the Structure–Function of Lactate Dehydrogenase from Mice Heart - Na Li; Yanmei Duan; Min Zhou; Chao Liu; Fashui Hong (Biological Trace Element Research, 2009)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Effects of Cerium on Key Enzymes of Carbon Assimilation of Spinach Under Magnesium Deficiency - Ze Yuguan; Zhou Min; Luo Luyang; Ji Zhe; Liu Chao; Yin Sitao; Duan Yanmei; Li Na; Hong Fashui (Biological Trace Element Research, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Genome-wide association scan for stature in Chinese: evidence for ethnic specific loci - Shu-Feng Lei; Tie-Lin Yang; Li-Jun Tan; Xiang-Ding Chen; Yan Guo; Yan-Fang Guo; Liang Zhang; Xiao-Gang Liu; Han Yan; Feng Pan; Zhi-Xin Zhang; Yu-Mei Peng; et al. (Human Genetics, 2009)

Phylogenetic Analysis of Leymus (Poaceae: Triticeae) Inferred from Nuclear rDNA ITS Sequences - Li-na Sha; Rui-wu Yang; Xing Fan; Xiao-li Wang; Yong-hong Zhou (Biochemical Genetics, 2008)

PolyQ-expanded ataxin-3 interacts with full-length ataxin-3 in a polyQ length-dependent manner - Na-Li Jia; Er-Kang Fei; Zheng Ying; Hong-Feng Wang; Guang-Hui Wang (Neuroscience Bulletin, 2008)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

Association study of the oestrogen signalling pathway genes in relation to age at natural menopause - Li-Na He; Dong-Hai Xiong; Yong-Jun Liu; Feng Zhang; Robert R. Recker; Hong-Wen Deng (Journal of Genetics, 2007)